Effects of apocynin, NADPH oxidase inhibitor, on levels of ADMA, MPO, iNOS and TLR4 induced by myocardial ischemia reperfusion - Ozcan, M.; Uysal, A.; Ozguler, I. M.; Burma, O.; Ilhan, N.; Sahna, E. (Wiley-Blackwell, 2014)
[Abstract Not Available]